IDENTIFIKASI KEBUTUHAN SARANA DAN PRASARANA PENJAS SMK DI GUNUNGKIDUL BERDASARKAN PERMENDIKNAS NO. 24 TAHUN 2007 - Yan Rangga Ardhimuna (Jurnal Pendidikan Jasmani Indonesia, 2010)
Abstract The purpose of this research was to know the layer of physical education tools and fields needed in SMK around Gunungkidul district with The Regulation of Indonesia National Education Department no. 24 th 2007 as the parameter. This research was a survey research in vocational schools in Gunungkidul with questionnaire as the data collection instrument. The populations are 38 vocational schools in Gunungkidul district, and 13 schools were chosen randomly as the sample. The data were analyzed through descriptive qualitative method. The result of the research shows that the layer of physical education tools needed by the vocational schools in Gunungkidul was high. On the other hand, the layer of physical education fields needed was at the average level. The detailed result of research could be mentioned as follows: the percentage of physical educations tools reached by the vocational schools in Gunungkidul district based on The Regulation of Indonesia National Education Department was 21.5%. The percentage of physical education fields reached was 39.7%. The low percentage of physical education tools reached shows how the high needs of physical education tools. Congruently, the average layer of physical education fields reached shows the average needs of physical education fields too. It influences the effectiveness of the teaching and learning process, so that an effort on fulfilling the ideal standard determined by our government was highly recommended. Kata kunci: kebutuhan, sarana dan prasarana, permendiknas